A-6 Childhood Adversity's Impact on Neurocognitive Functioning: Findings from South African Adolescents Living with HIV. (30th August 2021) - Santoro, Anthony F; Ferraris, Christopher; Phillips, Nicole; Hoare, Jacqueline; Robbins, Reuben N
Abstract: Objective: Childhood adversity (e.g., abuse/neglect) negatively affects neurocognitive functioning among people living with HIV (PLWH). However, less is known about this relationship among youth with perinatally-acquired HIV (PHIV) in low-and-middle-income countries, such as South Africa, many whom experience tremendous adversity in addition to living with a chronic, highly stigmatized disease. This study examined associations between adversity and neurocognitive functioning among South African adolescents (14–17 years) with PHIV. Method: 72 adolescents with PHIV (Mage = 15.63 years; 52.8% female) recruited from HIV clinics in Cape Town, South Africa completed the Adverse Childhood Experiences (ACE) scale and a tablet-based neurocognitive assessment. Controlling for age and sex, multiple regressions tested associations between ACE scores and processing speed, working memory, and executive functioning tests. T-tests assessed differences between participants exposed to high (≥2 ACEs) versus low (0–1 ACEs) adversity. Results: Adjusting for covariates, ACE scores predicted performance on tests of processing speed (Trail Making 1: B = 5.87, p = 0.001; Visual Discrimination 1: B = -1.01, p = 0.02; Visual Discrimination 2: B = -1.55, p = 0.002; Number Speed; B = 2.15, p = 0.02) and executive functioning (Inhibition errors: B = 1.27, p = 0.03), explaining 10–19% of variance in test scores. Significant differences between the high and low adversity groups on processing speed and executive functioning tests represented medium-to-large effects (d range = 0.51–1.11; Table 1). Conclusions: Childhood adversity predicts poorer neurocognitive functioning among youth with PHIV, specifically worse processing speed and executive functions – known drivers of functional outcomes among PLWH. Elucidating mechanisms by which adversity impacts neurocognitive functioning is critical to identify therapeutic targets and inform interventions to support neurocognitive health in PLWH across the lifespan.